The Role Of Work Discipline In Mediating Teamwork And Work Environment On Employee Performance (Study At The Property Office, PT. Graha Kreasi Medan) - Mukhlis Efendi; Mesra B (Lead Journal of Economy and Administration, 2023)
This study aims to investigate the role of work discipline in mediating the relationship between teamwork and work environment on employee performance in the property office of PT Graha Kreasi Medan. In the context of an increasingly competitive work environment, good employee performance is a key factor in achieving organizational goals. Therefore, it is important to understand the factors that affect employee performance, such as teamwork, work environment, and work discipline. This research will be conducted using a quantitative approach and survey method. The research sample will consist of employees working at PT Graha Kreasi Medan who are randomly selected. Data will be collected using a questionnaire covering the research variables, namely teamwork, work environment, work discipline, and employee performance. Data analysis will be carried out using statistical techniques such as regression and mediation analysis. The results of this study are expected to provide a better understanding of the relationship between teamwork, work environment, work discipline, and employee performance in property offices. In addition, this study can also provide practical recommendations for property office management in improving employee performance through the implementation of effective work discipline.